Lactogenic treatment effects on milk synthesis genes and protein secretion in cultured bovine mammary epithelial cells - Zahra Sattari; Søren Drud-Heydary Nielsen; Jing Che; Martin Krøyer Rasmussen; Yuan Yue; Stig Purup; Nina Aagaard Poulsen; Lotte Bach Larsen (Future Foods)
In a cellular agriculture context, the possibility of producing milk components using tissue derived bovine mammary epithelial cells (MEC) is an upcoming strategy being considered. As an essential step, development of an in-vitro model for optimizing lactogenic activity of cultured MEC is needed. MECs were isolated from bovine mammary tissue and cultured in a trans-well system. Treatment with differentiation media (DM) was performed for 7-days. Conditioned media containing the cell secretions (the “secretomes”) were collected, and the trans-epithelial-resistance (TEER), measured. On day 7 the cells were lysed, and expression of lactation associated genes were examined using qPCR. Proteomic analysis of the secretomes was performed using timsToF Pro LC-MS/MS. DM treated cells had significantly higher TEER for several days but a general decreasing trend started on day 4. Expressions of CSN1S1, CSN2, CSN3, ELF5 and PRLR were significantly increased after DM treatment. DM significantly altered the secretome's protein compositions. Numerous proteins involved in lactogenic activity of the MEC were identified. However, the DM did not significantly impact their peak intensities. These findings shed light on areas requiring additional refinement of the in-vitro model to enhance the production of milk components. These aspects primarily comprise the DM composition and experimental length.